Concurrent Infections Among Pyretic Children Seeking Treatment at Alupe Sub County Hospital, Busia County, Kenya - Mwongula, Albert W.; Siamba, Donald N.; Mwamburi, Lizzy A.; Mailu, Matilu (European Journal of Applied Sciences, 2023)
Fever is a frequently occurring medical symptom and may result from many divergent conditions ranging from mild to potentially serious. Children typically get high and fast – occurring fevers, reflecting the effects of the pyrogens upon an inexperienced immune system. Symptoms and signs of Chikungunya virus infections are quite similar to those of malaria and typhoid fever. Malaria and typhoid investigations are routinely carried out to establish the cause of pyrexia of unknown origin and treatment follows with complete neglect of Chikungunya virus infections. Thus, Chikungunya virus fever cases can sometimes be misdiagnosed or occur simultaneously with malaria, typhoid fever or both. This study was conducted to determine the concurrent infections of malaria and/or typhoid fever with Chikungunya virus, among febrile children aged 1 – 12 years seeking treatment in Alupe Sub County Hospital, Busia, Kenya. Blood smears were prepared for detection of malarial parasites and serum sample for widal test to detect typhoid fever. Enzyme-linked Immunosorbent Assay and Plaque Reduction Neutralisation Test were performed to detect the Chikungunya virus antibodies. The median age/interquartile range age for the febrile children was 4.5 years and 55.5% were female. Concurrent infections of Chikungunya virus with malaria or typhoid was 9.6% and 7%, respectively, using the Enzyme-linked Immunosorbent Assay technique and 10.5% and 9.9%, respectively, using Plaque Reduction Neutralisation Test. This supports the recommendation that Chikungunya virus should be tested for using both serological and molecular diagnostics in cases of patients presenting with fever.